An efficient SD-PAR technique for maximum power generation from modules of partially shaded PV arrays. (15th May 2019) - Satpathy, Priya Ranjan; Sharma, Renu; Dash, Sambit
Abstract: Partial shading is the most dominating problem faced by Photovoltaic (PV) arrays aiming to minimize the power generation of the system. This situation leads to multiple peak point formation in the characteristics curve of the array resulting failure of conventional maximum power point (MPP) trackers in tracking the global MPP of the system. This paper presents a static shade dispersion physical array relocation (SD-PAR) technique for PV arrays to minimize mismatch losses during partial shading that involves changing the position of modules to enhance the power generation under shading. SD-PAR reduces the power loss by distributing the shading effect throughout the PV array. The performance of SD-PAR technique is examined for an array of size 3 × 3 using MATLAB and prototype experiments under various artificially created shading conditions. SD-PAR is also compared for its efficiency in power generation with various hitherto known topologies such as Series-Parallel (SP), Bridge-Linked (BL) and Total Cross Tied (TCT). A comparison between Electrical Array Reconfiguration (EAR) and the proposed SD-PAR technique is done for a 5 × 5 PV array. It is found that SD-PAR exhibits a significant power enhancement characteristic in the arrays operating under different partial shading conditions compared to other hitherto known topologies and EAR. Highlights: A static SDPAR technique for PV modules for partial shading mitigation is proposed. Physical position of the modules is changed permanently without altering electrical configuration. SDPAR reduces the mismatch loss due to partial shading. SDPAR is evaluated under various shading conditions in MATLAB and field conditions. PV array with SDPAR technique excels in performance as compared to other hitherto known topologies.